MAKNA LEMPU' SEBAGAI KEARIFAN LOKAL DALAM PRAKTIK AKUNTANSI - Masradin, Masradin; Mukhtar, Afiah; Shafwah, Rif’ah; Wahyuni, Nur; Yacob Impak, Maya Indriani (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the meaning of Lempu' in Bugis culture and how this value is integrated into accounting practices, especially in forming professional ethics of accountants. A qualitative approach with ethnographic study methods was used to explore the value of Lempu’ in the context of local wisdom of the Bugis community. Data were collected through in-depth interviews with professional accountants, academics, and traditional figures in South Sulawesi. Data analysis was performed using NVivo 12. The results of the study indicate that Lempu' is a fundamental value in Bugis culture that is closely related to moral principles in accounting. This study identified ten main elements in Lempu', namely compliance with rules, courage, honesty, truth, admitting mistakes, moral principles, life principles, responsibility, personal dignity, and cultural identity and heritage. These findings reveal that the value of Lempu' has an important role in building transparency, accountability, and professionalism in Bugis community accounting practices. Therefore, an understanding of local cultural values ​​needs to be instilled in accounting education and practice to improve ethical standards in the accounting profession.